Formation of New Autonomous Regions in The Indonesian Constitutional System - Tubagus Fadli Kholifatul Umam; Fuqoha Fuqoha (IHSA Institute, 2025)
This study examines the formation of New Autonomous Regions (DOB) within Indonesia’s constitutional framework and analyzes the principles and impacts of the moratorium policy on DOB creation from legal and political perspectives. Grounded in the decentralization principle of the Unitary State of the Republic of Indonesia (NKRI), DOB formation aims to promote equitable development and enhance public services. However, the moratorium policy, in place since 2014, reflects concerns over fiscal burdens and regional readiness, creating tensions with local aspirations. Using a juridical-normative approach, the study reviews key legal frameworks, including the 1945 Constitution and Law Number 23 of 2014, alongside case studies of Papua, West Papua, and Sorong. Findings reveal that while the legal basis for DOB formation is clear, implementation faces administrative and political challenges. The moratorium, lacking a robust legal foundation, prioritizes national fiscal and political considerations over local needs, particularly in regions like Papua with strong demands for autonomy. The study underscores the need for a balanced, transparent approach to reconcile decentralization goals with effective governance